2000
DOI: 10.1111/j.1745-493x.2000.tb00249.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use and Impact of Communication Media in Purchasing and Supply Management

Abstract: SUMMARY Effective communication is a critical component of buyer‐supplier relationships. Purchasing professionals utilize a variety of media to communicate with suppliers, including phone, fax, face‐to‐face, mail, e‐mail, Internet, and electronic data interchange (EDI). The purpose of this research was to assess the impact of EDI and a variety of other media on buyer‐supplier relationships and performance. Analysis of the responses from a survey revealed that EDI is not living up to its promise. The results al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 22 publications
1
51
0
1
Order By: Relevance
“…Generally, such IT communications can be divided into e-mail, intranet, Internet, EDI, etc. (Larson and Kulchitsky 2000;Walczuch et al 2000;Stefansson 2002). …”
Section: It Communication and Its Benefitsmentioning
confidence: 97%
See 1 more Smart Citation
“…Generally, such IT communications can be divided into e-mail, intranet, Internet, EDI, etc. (Larson and Kulchitsky 2000;Walczuch et al 2000;Stefansson 2002). …”
Section: It Communication and Its Benefitsmentioning
confidence: 97%
“…Although it is certain that IT communication methods, such as e-mail, Internet, and EDI are very innovative methods, it is reasonable to say that IT communications will be complementary rather than a complete substitute for traditional communication methods such as mail, telephone and face-to-face meetings (Larson and Kulchitsky 2000). According to the 'media richness theory' concept developed by Lengel and Daft (1988), the level of information richness varies depending on the communication medium.…”
Section: It Communication Channel MIXmentioning
confidence: 99%
“…The creation of environment by means of the enactment strategy requires attempts to manipulate perceptions and issues and to impose ideas on the environment (Daft and Weick, 1984). Communications are an essential part of organizational boundary shifts (Tushman, 1977;Nonaka, 1994), yet, more important, they induce transformations beyond organizational boundaries, e.g., in marketing (Frazier and Summers 1984;Smith and Taylor 2004), supplier relation management (Takeishi, 2001;Larson and Kulchitsky, 2000), and institution-changing political activities (Hillman et al, 1999(Hillman et al, , 2004.…”
Section: Three Elements Of the Governed Niche Construction Strategymentioning
confidence: 99%
“…He further indicated that supplier lead time reduction minimizes the potential problem of shifting inventories to the supplier firm and eliminates quality problems associated with holding buffer inventories. Larson and Kulchitsky (2000) empirically found that lead time performance was affected by information quality and close relationships between the buying firm and the supplier firm.…”
Section: Supplier Lead Time Reductionmentioning
confidence: 99%